THE ROLE OF JOB SATISFACTION IN MEDIATING THE EFFECT OF JOB PLACEMENT, WORK ENVIRONMENT ADAPTATION, AND MOTIVATION ON TURNOVER INTENTION OF CONTRACT EMPLOYEES AT BANK XYZ INDRAMAYU - Viryal Iga Utari; Asti Nur aryanti; Gurawan Dayona; Nunung Ayu Sofiati; Widyastuti Nurmalia Utami (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The banking system is a crucial pillar in economic stability and faces intense competition in the era of globalization, demanding continuous innovation and effective human resource management (HRM). High Turnover Intention (TI) among contract employees, particularly in the Indonesian banking sector (reaching 15%-16%), poses a significant challenge. This issue is exacerbated by Work Placement policies that assign employees far from their domicile, triggering financial dissatisfaction (additional living costs) and fatigue (distance and travel time). This study aims to analyze and test the influence of the independent variables Work Placement, Work Environment Adaptation, and Work Motivation on the Turnover Intention of contract employees at Bank XYZ in Indramayu, by identifying the mediating role of Job Satisfaction. The research method uses a quantitative approach by distributing questionnaires to contract employees of Bank XYZ in Indramayu. The results of this study are expected to provide important information for Human Resource Management initiatives in formulating better employee placement and adaptation strategies, as well as enhancing motivation and job satisfaction.